Manajemen Wakil Kepala Bidang Kesiswaan dalam Meningkatkan Prestasi Akademik dan Non Akademik Peserta Didik di Madrasah Aliyah Hidayatul Mubtadiin Lampung Selatan - Hariyansah Hariyansah; Muhammad Yasin; Suci Hartati (Journal on Education, 2024)
The motivation behind this exploration is to decide the preparation of training in working on scholar and non-scholastic accomplishments at Mama Hidayatul Mubtadiin Jati Agung, the execution of understudy training in working on intellectual and non-scholastic accomplishments at Mama Hidayatul Mubtadiin Jati Agung and assessing the execution of understudy instructing in working on intellectual and non-scholastic accomplishments. at Mama Hidayatul Mubtadiin Jati Agung. This examination was led utilizing a subjective methodology. Scientists can straightforwardly figure out what's going on in the field, as per the issue plan. In gathering information, specialists utilized perception, meetings and documentation. Furthermore, the methods picked in information examination are information decrease, information show, and reaching determinations. The consequences of this exploration can be finished up as follows: (1) Improvement arranging is completed toward the start of every year. Through gathering exercises, examining what should be ready to make exercises like intellectual and non-scholastic fruitful. Beginning from admission to understudy graduation. And furthermore the dispersion of managers who are specialists in their fields to direct understudies in accomplishing both scholar and non-scholastic accomplishments. (2) Execution of training, to be specific: Scholarly, execution of instructing in the scholastic field is completed consistently. The execution of training incorporates recognizing understudy knowledge and potential, directing choice, giving inspiration, giving supporting offices.